2016
DOI: 10.1038/cdd.2016.45
|View full text |Cite
|
Sign up to set email alerts
|

Proline isomerisation as a novel regulatory mechanism for p38MAPK activation and functions

Abstract: The stress-induced p38 mitogen-activated protein kinase (MAPK) pathway plays an essential role in multiple physiological processes, including cancer. In turn, p38MAPK phosphorylation at Thr180 and Tyr182 is a key regulatory mechanism for its activation and functions. Here we show that this mechanism is actively regulated through isomerisation of Pro224. Different cyclophilins can isomerise this proline residue and modulate the ability of upstream kinases to phosphorylate Thr180 and Tyr182. In vivo mutation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…However, noticeable cardiac toxicity due to p38 MAPK inhibitors suppressing the benefits of endogenous p38 MAPK activity hinders its application [21,22]. Recently, some noncanonical MAPK kinase-independent activation mechanisms were identified [34][35][36]. Specifically, p38 MAPK autophosphorylation via binding to TGF-β-activated protein kinase 1-binding protein is the mechanism that activates p38 MAPK during myocardial ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…However, noticeable cardiac toxicity due to p38 MAPK inhibitors suppressing the benefits of endogenous p38 MAPK activity hinders its application [21,22]. Recently, some noncanonical MAPK kinase-independent activation mechanisms were identified [34][35][36]. Specifically, p38 MAPK autophosphorylation via binding to TGF-β-activated protein kinase 1-binding protein is the mechanism that activates p38 MAPK during myocardial ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…As chemotherapy is a powerful inducer of P38MAPK activity, the use of either P38 or HA inhibitors could significantly inhibit the cancer activity of the tumor microenvironment. From a therapeutic standpoint, the best approach to target HA-mediated tumor progression could be by blocking P38MAPK with pharmacological inhibitors, inhibiting HA synthesis targeting hyaluronidases, or disrupting HA-receptor interactions [ 23 ]. At present, fundamental research about effective methods of treatment of esophageal carcinoma is ongoing, and there still are many pending disputes and question needing to solve [ 24 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the ATR-L is a prolyl trans -isomer of cytoplasmic ATR while ATR-H is the cis -isomer 40 . The formation of cytoplasmic ATR-L ( trans -ATR) from ATR-H ( cis -ATR) is mediated by peptidylprolyl cis/trans isomerase NIMA-interacting 1 (Pin1) 40 ; this enzyme is a critical regulator of many biological processes in both normal and diseased cells 4248 . Since ATR is naturally more stable in its cis -isomeric form, newly-synthesized ATR is in the ATR-H isoform but is quickly converted to the ATR-L isoform by Pin1 isomerization of the phospho- Ser 428-- Pro 429 site of the ATR protein 40 .…”
Section: Atr Signaling Mediates the Cellular Response To Dna Damaged mentioning
confidence: 99%